Measuring Occupational Performance : Supporting Best Practice in Occupational Therapy - Law, Mary, ....-; Baum, Carolyn Manville, ....-; Dunn, Winnie, ....- (Thorofare (N.J.) : Slack, 2005)
As the profession of occupational therapy continues to mature and expand its practice, the measurement of occupational performance is one of the key avenues that all practicing clinicians will need to explore and master. A complex subject for the new and practicing occupational therapist, each step in the evaluation process from assessment to interpretation to intervention is critical. Having one solid, evidence-based textbook to teach and guide in the measurement process is welcome. With an emphasis on the context of current best practice, Measuring Occupational Performance: Supporting Best Practice in Occupational Therapy rises to meet this challenge in an updated and expanded second edition. // Three of the professions most recognized and leading professionals, Drs. Mary Law, Carolyn M. Baum, and Winnie Dunn, have joined together to bring their expertise in assessing occupational performance to the pages of the second edition of Measuring Occupational Performance. With a more focused
Approach on evidence based rehabilitation and accountability, the student will be guided throughout their educational career by learning to identify the best approach for outcome measurement. New to the second edition: * A new focus that accounts for the profession's shift to evidence based rehabilitation and occupation. * Updated and restructured measures that allow this to be the only resource needed for measuring occupational performance. * Streamlined tables for easy access to information and are now located at the conclusion of each chapter.* An added chapter on participation measures. New appendices that list measures by author and test name allow for easy navigation through an array of topics, including conducting assessments, interpreting measurement information, and strategies for using assessment information. The addition of an Instructor's Manual containing case scenarios, activities, and assignment ideas for the classroom. // Measuring Occupational Performance provides easily
Accessible, up-to-date information for all occupational performance measures, including a systematic, detailed focus on measures important for evidence-based occupational therapy. Measurement issues and practices are discussed, and a decision-making framework is provided to guide the choice of assessment tools. This timely work helps to simplify a complex subject, and is a must-have for both occupational therapy students and practitioners. // Instructor's Manual: Instructors: Visit our new website created especially for you at www.efacultylounge.com! Through this website you will be able to access a variety of materials including, Measuring Occupational Performance, Instructor's Manual. Available on-line, this exciting manual provides additional case study information, objectives for study, lab activities, guiding questions, andreferences. Contents: Dedication // Acknowledgments // About the Editors // Contributing Authors // Preface // Foreword SECTION I: FOUNDATIONS OF OCCUPATIONAL THERAPY
MEASUREMENT PRACTICE / SECTION II: MEASUREMENT IN OCCUPATIONAL THERAPY // SECTION III: USING MEASUREMENT IN PRACTICE // Appendices: Appendix A: List of Measures (Alphabetical) / Appendix B: List of Measures by Occupational Performance Area / Appendix C: List of Measures by Source/Author / Appendix D: List of Measures Mapped to the International Classification of Functioning / Appendix E: Outcome Measures Rating Forms and Guidelines / Index
Keywords: Ergotherapie -- Adviseren; Ergotherapie; Evidence based practice -- Ergotherapie